Homossexualidades na territorialidade tradicionalista gaúcha - Göergen, Edipo Djavan dos Reis (2017)
The Traditionalist Movement of Rio Grande do Sul (MTG) starts in the decade of 1940, in the city of Porto Alegre, aiming to spread, by means of cultural manifestations, the daily practices of the countryside life of the ancient inhabitants of this state. The traditionalism soon went beyond its first entity. There are, nowadays, Centers of Tradition of Rio Grande do Sul (CTG) all over the national territory. Their manifestations value and stimulate the reproduction of the everyday lifestyle of the old families from the state, which have a heteronormative assumption that, consequently, spread conservative and sexist ideals in their spatialities. The author of this work is homosexual and also participated in traditionalist entities during a period of his life, noticing sexist and homophobic discourses coming from his peers during that time, which aroused curiosity in the researcher in the face of such a paradox. Thus, this work is interested in understanding how the homosexualities of gay men are manifested while they take part in the Tradicionalist Movement. By using the category of geographic analysis of territory (SACK, 1986; BONNEMAISON, 2002; RAFFESTIN, 1993), this study attempts to relate it with the Rio Grande do Sul traditionalism and, consequently, with the Traditionalist Movement of the state. Therefore, the MTG was regarded as a territoriality and the Centers of Tradition (CTG) and their events as territories. The understanding of such territories happened through identity manner (CLAVAL, 1999), being the traditionalist territories nuclei of spreading identity conceptions which are conservative, sexist and heteronormative. As homosexuals are observed in spaces of tradicionalism of Rio Grande do Sul, it's possible to see that the tradionalist identity, like the other ones, is not homogeneous, enabling intersections of different identities (WOODWARD, 2014). Considering the participation of the homosexual identity in this work, its social territorializations are noticed, and this study, if possible, identifies them on the fringes of the traditionalist territories, contradicting conservative hegemony in its central portions. Aiming to make visible such group that is socially marginalized, this investigation has a theorical base to the geographic field of Feminist and Queer Geography (SILVA, 2009), which presents similar positions to the field of post-phenomenology (MARANDOLA JR., 2013) that expands the studies of fenomenological base, enabling us to perceive subject as a result of the environment where he/she lives, being, therefore, discursively constructed (BUTLER, 2008). The data for this research was collected by having interviews, taking into account to observe the homosexual reality inside the traditionalist environment. The Discourse Analysis (ORLANDI, 2012; PÊCHEUX, 1997) was used as the method to analyze the collected corpus, trying to understand its social marks and identity positionalities. This way, it was possible to conclude that the majority of the interviewees, despite being homosexuals, have discursive practices that agree with traditionalism, that is, views that point out sexist, heteronormative and homophobic discourses expressed in their speech, which can be a reason for them to remain inside traditionalist territories. However, it is also possible to see some central and marginalized settings (SILVA, 2007) in the mentioned territories, ensuring the existence of homoerotic microterritorializations (COSTA, 2012) on the fringes of the traditionalist territoriality of Rio Grande do Sul, contrasting with its conservative center, as well as there are some subjects that break off the agreements pre-established by traditionalism, manifesting their sexuality until they are required to adjust their behavior.